PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL DENGAN MEMBUAT MIND MAP DI KELAS V SD NEGERI 07 ULAK KARANG SELATAN - Putri, Rhezi Dhita; Arwin, Arwin; Eliyasni, Rifda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research is motivated by the fact in Ulak Karang Selatan 07 Public Elementary School that teachers are more dominant in the learning process than students so that students become passive, students are less enthusiastic in learning. The purpose of this study was to describe how planning and implementing the learning of Social Sciences by making Mind Map in class V SD SD 07 Ulak Karang Selatan. Classroom action research uses qualitative and quantitative approaches. In its implementation, this research was carried out in two cycles. The research procedure consists of planning, implementing, observing and reflecting. The results of the study were the results of RPP observation in the first cycle was 80.5% (B) increased in the second cycle to 91.7% (SB). In the implementation of teacher learning aspects of cycle I is 71.3 (C) an increase of 92.5% (SB) in cycle II and aspects of students in cycle I is 71.3 (C) an increase of 92.5% (SB) cycle II. Thus making Mind Map can improve the learning process of social science students in class V SD Negeri 07 Ulak Karang Selatan.